EFISIENSI PRODUKSI DAN PENDAPATAN BUDIDAYA UDANG VANNAME DENGAN SUMBER MODAL BUSB DI KECAMATAN RAWAJITU TIMUR - Ishmah Nurhidayati; Dyah Aring Hepiana Lestari; Teguh Endaryanto (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
The study aims to analyze the partnership pattern between BUSB and shrimp farmers, factors that affect production of vanname shrimp, technical efficiency and factors that affect technical inefficiency, allocative and economic efficiency, and income of vanname shrimp farming.  The population used in this research was members of the BUSB with the last harvesting age of 71-75 days in order to obtain a total sample of 55 people.  The analysis was conducted descriptively using the Stochastic Frontier analysis and income analysis.  The results showed that the partnership between the sub-block business entities and farmers is the Agribusiness Operational Cooperation pattern.  The factors that affected vanname shrimp production were shrimp fry, feed, and diesel fuel.  The vanname shrimp farming is not technically and economically efficient with the average efficiency value of 0.26 and 0.20, but allocatively efficient with the average efficiency value of 0.78.  The vaname shrimp farming is profitable for farmers with R/C value over cash costs of 1.44 and over total cost of 1.15. Key words : income, partnership, production efficiency, shrimp